Alcohol acyltransferase gene and ester precursors differentiate composition of volatile esters in three interspecific hybrids of Vitis labrusca × V. Vinifera during berry development period. (15th October 2019) - Qian, Xu; Liu, Yaran; Zhang, Guojun; Yan, Ailing; Wang, Huiling; Wang, Xiaoyue; Pan, Qiuhong; Xu, Haiying; Sun, Lei; Zhu, Baoqing
Highlights: Moldova contained lowest content of volatile esters. The composition of volatile esters in Campbell Early and Catawba were different. AAT gene mainly determined the contents of volatile esters. Precursors and precursor genes also alter biosynthesis of volatile esters. Abstract: This study investigated the accumulation of esters in three hybrid grape cultivars during berry development under two vintages to elucidate the differentiation on their esters biosynthesis. Results showed 'Moldova' showed lower esters content than 'Campbell Early' and 'Catawba' resulting from its limited AAT gene expression and 20 different encoded amino acids. The volatile esters compositions of 'Campbell Early' and 'Catawba' in both vintages were different. Correlation analysis revealed that concentrations of hexyl acetate, 2-phenethyl acetate, ethyl ( E, E )-2, 4-hexadienoate and ethyl phenylacetate were related to their corresponding alcohols level, whereas threonine and alanine affected ethyl heptanoate formation. Transcriptome analysis indicated that 1847, 1781 and 1870 DEGs, at E-L 35, 36 and 38, respectively, were characterized between 'Campbell Early' and 'Catawba'. The expression level of genes related to the volatile ester precursors biosynthesis, including PRX-VIT_211s0016g05320, PAO-VIT_217s0000g09100, ACOX-VIT_212s0028g02660, ACOX-VIT_216s0022g01120, echA-VIT_205s0077g00860 and ACOX-VIT_200s0662g00010, exhibited a positive correlation to the concentrations of their corresponding volatile esters.